Chronic heat stress part 1: Decrease in egg quality, increase in cortisol levels in egg albumen, and reduction in fertility of breeder pekin ducks - Oluwagbenga, E. M.; Tetel, V.; Schober, J.; Fraley, G. S. (Frontiers in Physiology, 2022)
Global warming poses detrimental effects on poultry production leading to substantial economic losses. The goal of our experiment was to test the hypothesis that heat stress (HS) would alter welfare and egg quality (EQ) of breeder ducks. Furthermore, we wanted to test if HS would increase cortisol levels in egg albumen. Adult Pekin ducks were randomly assigned to two different rooms at 85% lay with 60 hens and 20 drakes per room. Baseline data including body weight, body condition scores (BCS), and egg production/quality were collected the week preceding heat treatment. Ducks were subjected to cyclic HS of 35oC for 10h/day and 29.5oC for the remaining 14h/day for 3 weeks while the control room was maintained at 22oC. Eggs were collected daily and analyzed weekly for quality assessment, and for albumen glucocorticoid (GCs) levels using mass spectrometry. One week before the exposure to HS, 10 hens and 5 drakes were euthanized and the same number again after 3 weeks and birds necropsied. Data analyses were done by 1- or 2-way ANOVA as appropriate with a Tukey-Kramer post hoc test. BCS were analyzed using a chi-squared test. A p ≤ 0.05 was considered significant. Circulating levels of corticosterone were significantly (p < 0.01) elevated at week 1 only in the HS hens. The circulating levels of cortisol increased significantly at week 1 and 2 (p < 0.05), and week 3 (p < 0.01) in the hens and at weeks 2 and 3 only (p < 0.05) in the drakes. Feather quality scores (p< 0.01), feather cleanliness scores (p<0.001) and footpad quality scores (p<0.05) increased significantly in the HS group. HS elicited a significant (p<0.001) decrease in egg production at weeks 1 and 3. Hens in the HS group showed significantly decreased BW (p<0.001) and number of follicles (p<0.05). Shell weight decreased significantly at week 1 only (p<0.05) compared to controls. Yolk weight decreased significantly at week 3 (p<0.01) compared to controls. HS elicited a significant increase in albumen cortisol levels at week 1 (p<0.05) and week 3 (p<0.05). Thus, cortisol may provide critical information to further understand and to improve welfare.